Acceleration of 60 MeV proton beams in the commissioning experiment of the SULF-10 PW laser. (3rd August 2022) - Li, A. X.; Qin, C. Y.; Zhang, H.; Li, S.; Fan, L. L.; Wang, Q. S.; Xu, T. J.; Wang, N. W.; Yu, L. H.; Xu, Y.; Liu, Y. Q.; Wang, C.; et al.
Abstract: We report the experimental results of the commissioning phase in the 10 PW laser beamline of the Shanghai Superintense Ultrafast Laser Facility (SULF). The peak power reaches 2.4 PW on target without the last amplifying during the experiment. The laser energy of 72 ± 9 J is directed to a focal spot of approximately 6 μm diameter (full width at half maximum) in 30 fs pulse duration, yielding a focused peak intensity around 2.0 × 10 21 W/cm 2 . The first laser-proton acceleration experiment is performed using plain copper and plastic targets. High-energy proton beams with maximum cut-off energy up to 62.5 MeV are achieved using copper foils at the optimum target thickness of 4 μm via target normal sheath acceleration. For plastic targets of tens of nanometers thick, the proton cut-off energy is approximately 20 MeV, showing ring-like or filamented density distributions. These experimental results reflect the capabilities of the SULF-10 PW beamline, for example, both ultrahigh intensity and relatively good beam contrast. Further optimization for these key parameters is underway, where peak laser intensities of 10 22 –10 23 W/cm 2 are anticipated to support various experiments on extreme field physics.